2014
DOI: 10.7314/apjcp.2014.15.21.9487
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Discrepancies between Radiological and Pathological Size of Hepatocellular Carcinoma Masses

Abstract: Asian Pac J Cancer Prev, 15 (21), 9487-9494 IntroductionTumor size of hepatocellular carcinoma (HCC) is an important indicator for prognostic assessment and the choice of treatment, and also be a critical variable in staging systems. Although the prognosis of HCC is extremely complicated and depends not only on the stage of the tumor, but also on the residual liver function and serum a-fetoprotein (AFP) levels (Xu et al., 2012) AbstractBackground: The size of a hepatic neoplasm is critical for staging, progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…Edmondson–Steiner grades, Child-Pugh grades, and tumor size were closely related to HCC. [1820] Songlin et al [21] revealed the association between AFP and clinicopathological features of HCC, including Child-Pugh grades and tumor size, which was consistent with our findings. In other studies, the relationship between hematologic parameters (NLR and GPR) and clinical characteristics (Child-Pugh grades and tumor size) has been demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…Edmondson–Steiner grades, Child-Pugh grades, and tumor size were closely related to HCC. [1820] Songlin et al [21] revealed the association between AFP and clinicopathological features of HCC, including Child-Pugh grades and tumor size, which was consistent with our findings. In other studies, the relationship between hematologic parameters (NLR and GPR) and clinical characteristics (Child-Pugh grades and tumor size) has been demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…Child‐Pugh grades, and tumor size were closely related to HCC. 30 , 31 , 32 Songlin et al 33 revealed the association between AFP and clinicopathological features of HCC, including Child‐Pugh grades and tumor size, which was consistent with our findings. In other studies, the relationship between hematologic parameters (GAR and GAPR) and clinical characteristics (Child‐Pugh grades and tumor size) have been demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies show a discrepancy between radiological and pathologic size measurements of hepatic and renal tumors and, likewise, studies involving pancreatic tumors have illustrated a similar lack of correlation between radiological measurement and pathologic size [ 18 , 30 , 31 , 32 , 33 ]. For example, Maimone et al used MRCP to measure IPMN long-axis diameter in comparison to pathology and reported size differences ranging from 2–44 mm with a mean difference of 5.88 mm, while Lee, Y.S.…”
Section: Introductionmentioning
confidence: 99%